2021
DOI: 10.9738/intsurg-d-20-00036.1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Completion Total Gastrectomy as a Standardized Procedure for Gastric Stump Cancer: A Case Control Study

Abstract: Objective Complete gastrectomy for gastric stump cancer (GSC) can be challenging due to severe adhesions; therefore, advanced techniques are required when being performed by laparoscopic surgery. This study aimed to evaluate the clinical outcomes of laparoscopic completion total gastrectomy (LCTG) for the treatment of GSC. Methods Patient records from January 2010 to October 2018 were retrospectively evaluated. The patients were classified into two groups depending on whether they underwent open or laparoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Eleven studies sought to compare the outcomes of laparoscopy versus laparotomy, while two studies compared the outcomes of laparoscopy versus robotic‐assisted laparoscopy (Figure 1). Since the index report of laparoscopic completion by Yamada et al in 2015, there were 596 reported cases (including our study) of planned laparoscopic completion gastrectomy 4–6,11–30 . The mean age of patients was 68.3 years and interval to completion was 21.8 years.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…Eleven studies sought to compare the outcomes of laparoscopy versus laparotomy, while two studies compared the outcomes of laparoscopy versus robotic‐assisted laparoscopy (Figure 1). Since the index report of laparoscopic completion by Yamada et al in 2015, there were 596 reported cases (including our study) of planned laparoscopic completion gastrectomy 4–6,11–30 . The mean age of patients was 68.3 years and interval to completion was 21.8 years.…”
Section: Resultsmentioning
confidence: 73%
“…Since the index report of laparoscopic completion by Yamada et al in 2015, there were 596 reported cases (including our study) of planned laparoscopic completion gastrectomy. [4][5][6][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The mean age of patients was 68.3 years and interval to completion was 21.8 years. There were 146 (38.6%) cases with prior benign gastric disease, while 232 had prior malignant disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations